Moving through the political participation hierarchy: A focus on personal values - Gail Pacheco; Barrett Owen (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2013)
This study empirically explores the determinants of political participation. Using recent data from the European Social Survey (2010/2011), we investigate the relationship between political participation and personal values, via use of the Schwartz (1992) values inventory. Political activities are categorised into levels of participation (none, weak, medium, strong) based on the cost of participating and how unconventional the activity is. A generalised ordered logit model is applied, and finds that individuals that are more open to change and more self-transcendent, are more likely to participate. Furthermore, the patterns of influence (with respect to the majority of individual characteristics) are not monotonic in nature, as you rise through the levels of political participation, highlighting some key areas that future research could tackle. These findings are important for researchers and policy makers who may be interested in understanding determinants of, and/or enhancing the level of political participation in an economy.
Keywords: D72; P16; 330; personal values; political participation